Housing First and Social Integration: A Realistic Aim? - Quilgars, Deborah (Social Inclusion, 2016)
Housing First is now dominating discussions about how best to respond to homelessness among people with high and complex needs throughout the EU and in several countries within the OECD. Whilst recognised internationally as an effective model in addressing homelessness, little attention has been given as to whether Housing First also assists previously homeless people become more socially integrated into their communities. This paper reviews the available research evidence (utilising a Rapid Evidence Assessment methodology) on the extent to which Housing First services are effective in promoting social integration. Existing evidence suggests Housing First is delivering varying results in respect of social integration, despite some evidence suggesting normalising effects of settled housing on ontological security. The paper argues that a lack of clarity around the mechanisms by which Housing First is designed to deliver ‘social integration’, coupled with poor measurement, helps explain the inconsistent and sometimes limited results for Housing First services in this area. It concludes that there is a need to look critically at the extent to which Housing First can deliver social integration, moving the debate beyond the successes in housing sustainment and identifying what is needed to enhance people’s lives in the longer-term.